2022
DOI: 10.1096/fj.202101703r
|View full text |Cite
|
Sign up to set email alerts
|

Physical radiofrequency adjuvant enhances immune responses to influenza H5N1 vaccination

Abstract: Pre‐pandemic influenza H5N1 vaccine has relatively low immunogenicity and often requires high antigen amounts and two immunizations to induce protective immunity. Incorporation of vaccine adjuvants is promising to stretch vaccine doses during pandemic outbreaks. This study presents a physical radiofrequency (RF) adjuvant (RFA) to conveniently and effectively increase the immunogenicity and efficacy of H5N1 vaccine without modification of vaccine preparation. Physical RFA is based on a brief RF treatment of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…RFA boosts seasonal influenza vaccination. Our previous studies found the physical RFA could enhance the efficacy of influenza pandemic 2009 H1N1 vaccine, split virion H5N1 vaccine, and intracellular NP/M1 vaccine [18][19][20] . It remained to be explored whether RFA was also effective to boost seasonal influenza vaccination.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…RFA boosts seasonal influenza vaccination. Our previous studies found the physical RFA could enhance the efficacy of influenza pandemic 2009 H1N1 vaccine, split virion H5N1 vaccine, and intracellular NP/M1 vaccine [18][19][20] . It remained to be explored whether RFA was also effective to boost seasonal influenza vaccination.…”
Section: Resultsmentioning
confidence: 99%
“…Hair on the lateral back skin of mice was removed one day before experiment by clipping and application of hair-removal lotion. Next day, hair-removed skin was exposed to RF or sham treatment followed by ID injection of vaccine into RF-or sham-treated skin as in our previous reports [18][19][20] . In chemical adjuvant groups, mice were intramuscularly injected with the same amount of vaccine in the presence of AddaVax (50%, vol/vol) except otherwise specified.…”
Section: Immunizationmentioning
confidence: 99%
“…RFA was also effective to boost intradermal H5N1 immunization in both male and female mice ( Li et al, 2022 ). Intradermal H5N1 vaccine in the presence of RFA (RFA/ID) induced significantly higher serum HI titer and IgG antibody titer than intradermal vaccine alone (ID) ( Li et al, 2022 ). After lethal viral challenges, RFA/ID but not ID group showed significantly reduced lung viral titer ( Li et al, 2022 ).…”
Section: Radiofrequency Adjuvantmentioning
confidence: 99%
“…Intradermal H5N1 vaccine in the presence of RFA (RFA/ID) induced significantly higher serum HI titer and IgG antibody titer than intradermal vaccine alone (ID) ( Li et al, 2022 ). After lethal viral challenges, RFA/ID but not ID group showed significantly reduced lung viral titer ( Li et al, 2022 ). Interestingly, significantly higher TNFα and IFNγ-secreting CD4 + and CD8 + T cells were found in the lung after challenge in RFA/ID group as compared to ID group.…”
Section: Radiofrequency Adjuvantmentioning
confidence: 99%
“…Intradermal (ID) immunization was used in our study to elicit better immune responses than traditional intramuscular immunization [19]. For accurate ID immunization, hair on the lateral dorsal skin of mice was removed one day before the experiment as shown in our recent studies [20,21]. Next day, aged mice were intradermally immunized with 0.5 µg pdm09 vaccine (HA equivalent) alone or in the presence of 40 µg CpG 1018 or left non-immunized.…”
Section: Immunizationmentioning
confidence: 99%